The impact of intellectual disabilities on elite sports performance - Burns, J. (International Review of Sport and Exercise Psychology, 2015)
Athletes with intellectual disabilities (ID) were re-introduced into the Paralympics in London 2012. As part of this development a classification system had to be established evidencing the impact this impairment has on elite sports performance. This review examines the research behind this issue. Firstly it examines the limited literature comparing the standards reached by top-level athletes with ID with those without disabilities, and then moves on to look at the research demonstrating differences in both the cognitive and physical skills needed for elite performance. The article then reviews the factors that may be implicated to account for this disparity, from a range of perspectives. A case is made for the importance of looking at this area in terms of the potential for the transferability of research findings from this group to talent identification in mainstream athletes and the benefits of integrating neuropsychological concepts and approaches to understanding the cognitive components behind the development of particular skills associated with high-level performance in specific sports.